PENGARUH SERVICESCAPE TERHADAP SERVICE PERFORMANCE DAN CUSTOMER SATISFACTION PADA PELABUHAN KELAS IV PELINDO I CABANG RENGAT, KABUPATEN INDRAGIRI HULU, PROVINSI RIAU - Kurniawan, Rieskie; Zulkarnain, Zulkarnain; Rustam, Bambang Rianto (Jurnal Tepak Manajemen Bisnis, 2018)
The study conducted in Pelindo I Rengat branch or known as PelabuhanRengat. The purpose is to know the direct and indirect influence of servicescapetowards customer satisfaction through service performance as the mediating variable.Population are port users of Pelabuhan Rengat consists of 73 users. Samples taken bycensus to all port users of Pelabuhan Rengat. Variables used are servicescape asexogenous, customer satisfaction as endogeneus, and service performance as themediating variable. Data analyzed by using descriptive and SEM-PLS that assisted byWarpPLS 5.0. The study reveals that servicescape significantly influences serviceperformance, but not significantly towards customer satisfaction. Service performancehas significant influence towards customer satisfaction. Servicescape has indirectinfluence towards customer satisfaction mediated by service performance. Optimizingthe quality of servicescape and enhancing the service performance may potentiallyimprove port userâs satisfaction.